أداء وسيط التبادل التجاري على وضعية التجارة الخارجية : دراسة حالة الجزائر - بضياف، صالح (جامعة لونيسي علي البليدة 2 - مخبر التنمية الاقتصادية والبشرية, 2017)
Is the exchange rate of controlling the global trade, especially in recent factors, which has become a bourse called the Stock Exchange currencies are handled between the various dealers from all over the globe to meet the desires of investors and dealers trading and the various parties intereste in the currency. The latter has become has several effects on the foreign trade of the countries, including Algeria, which seeks through which to influence the export and import sector, based on the latest of several economic reforms explain to the new economic model that will clarify the features in the year 2019 The theme of our research deals with knowledge of the performance of the exchange rate in Algeria, the most important consequences associated with the financial situation of the country, and that light was asked the following question: Is the performance of the exchange rate contributes to the lifting of th proceed of foreign trade Algeria?.
سعر الصرف ما هو إلا وسيط للتبادل ومقياسا للقيمة في المعاملات الاقتصادية والتجارية، والتي عادة ما تتم بين الأعوان الاقتصادية داخل وخارج البلد إلا أن هذه الوظائف تبقى مقرونة بمدى فعالية السياسة المختارة ووفق ما تملكه البلاد من إمكانيات ومستوى مرونة الاقتصاد للتحولات الاقتصادية الدولية وللمتغيرات الجيوستراتيجية في العصر الحالي. ومن أجل ذلك ازداد اهتمام الجزائر لموضوع سعر صرف الدينار الجزائري أمام العملات الأجنبية ومدى اختيار السياسة الأنجح لتنشيط حركية المعاملات التجارية والاقتصاد التصديري خاصة في الشق القانوني وتقريب وجهات النظر بين بنك الجزائر ووزارة التجارة ووزارة المالية. وموضوع بحثنا يتناول معرفة أداء سعر الصرف في الجزائر وأهم التداعيات المصاحبة على الوضع المالي للبلاد من خلال أسقاط الصورة على وضعية تجارتها الخارجية، وعلى ضوء ذلك تم طرح التساؤل التالي: هل سعر الصرف المطبق في الجزائر يساهم في الرفع من حصيلة التجارة الخارجية للبلد؟
Keywords: الدينار الجزائري; التجارة الخارجية; سعر الصرف; التبادل التجاري; الجزائر